2013
DOI: 10.3329/jdmc.v21i1.13232
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ethanolic extract of leaf and seed of Tamarindus indica on paracetamol induced hepatotoxicity in rats

Abstract: DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13232 J. Dhaka Med. Coll. 2012; 21(1): 12-15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Most studies that use medicinal plants show effects similar to those found in this study [11][12][13][14][15] , however all perform prophylactic treatment of toxic hepatitis, similar to PCG1 and PCG7. However, studies should focus on the analysis of the therapeutic effect of the oils, whereas hardly identifies the patients who abuse acetaminophenin before they show hepatitis.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Most studies that use medicinal plants show effects similar to those found in this study [11][12][13][14][15] , however all perform prophylactic treatment of toxic hepatitis, similar to PCG1 and PCG7. However, studies should focus on the analysis of the therapeutic effect of the oils, whereas hardly identifies the patients who abuse acetaminophenin before they show hepatitis.…”
Section: Discussionsupporting
confidence: 50%
“…The acetaminophenin the dose used, showed hepatotoxic effects perceived by increased dosage of ALT and AST in the control group 11,12,14 , and the copaiba oil showed no effects when administered prophylactically during a day, however for 7 days and prophylactic therapy showed similar results to those animals treated with N-Acetyl-Cysteine, showing a hepatoprotective potential of this oil.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations